Seasonal variations of sea breeze and its effect on the spectral behaviour of surface layer winds in the coastal zone near Visakhapatnam, India. (May 2019) - KiranKumar, N.V.P.; Jagadeesh, K.; Niranjan, K.; Rajeev, K.
Abstract: Seasonal variation of sea breeze (SB) characteristics and its effect on turbulence spectra at Visakhapatnam (17.7°N, 83.3°E) located at east coast of Peninsular India are investigated by considering 244 sea breeze events during December 2012 to March 2014. The delayed onset of backdoor SB during winter occurs due to the southward component of shore-parallel background winds while the prevailing northward component of background wind enable the early onset of corkscrew SB during pre-monsoon and summer monsoon. The turbulence spectral peak of horizontal winds shifts to higher frequency side after SB onset. Highlights: Seasonal variation of sea breeze (SB) characteristics and its effect on turbulence spectra at a coastal station, Visakhapatnam (17.7°N, 83.3°E) located in the east coast of Peninsular India are investigated using fast-response micro-meteorological observations carried out at 10 m level during December 2012 to March 2014. The study is based on 244 days with unambiguous identification of sea breeze circulation and brings out the following highlights: Sea breeze activity exists more or less throughout the year, though it is most prominent in winter and rather weak during summer monsoon season. The most probable onset time of sea breeze is between 08 and 11 LT during winter and around 07–10 LT during pre-monsoon and summer monsoon seasons. The prevailing wind direction and diurnal variation of winds observed at Visakhapatnam show that the occurrence of pure or backdoor sea breeze (the later characterized by veering of wind and potentially delayed sea breeze onset) might be more frequent during winter while corkscrew sea breeze (characterized by backing of wind and early sea breeze onset) might be more frequent during pre-monsoon and summer monsoon seasons. The turbulence spectral peak of horizontal winds shifts to higher frequency side after SB onset, due to the development of thermal internal boundary layer.